Ein amharischer Atlas aus Malta - Wagner, Ewald (Aethiopica, 2010)
In August 2008 Professor Dr. Hans H. Kaminsky of the Institute of History of the University of Giessen, gave me an Amharic atlas, printed in Malta, which he had bought several years ago, at the Giessen flee-market. The atlas is now in the possession of the Hiob Ludolf Zentrum für Äthiopistik of the Asien-Afrika-Institut, Universität Hamburg. The article places the atlas into the historical context of the educational efforts of German protestant missionaries who worked under the auspices of the Church Missionary Society in Ethiopia, during the first half of the 19th century. It also sheds light on the Society’s printing activities in Malta.